Assesment of Antibiotic Prescribing Practices in Hospital X, Malang Regency: A Gyssens Method - Erna Susanti; Ellyvina S. Dhini (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Antibiotic resistance remains a major problem in medicine. The therapy and goals of antibiotic treatment given to patients do not meet the expected therapeutic targets due to the occurrence of antibiotic resistance. The long-term goal of this study is to achieve the rationality of antibiotic use based on the results of a qualitative analysis of antibiotic use at Hospital X, Malang Regency using the Gyssen method. The main goal to be achieved is to prevent antibiotic resistance in hospitals due to irrational use. The specific objective of this study is to assess the appropriateness of antibiotic use among patients in the Internal Medicine, surgical, and obstetrics-gynecology departments based on Gyssens criteria. This study uses a retrospective descriptive method to provide a general overview of antibiotic use at Hospital X, Malang Regency. The sample consisted of patient medical records and antibiotic administration record data, including 50 internal patients, 50 surgical patients, and 40 Obgyn patients. The results showed that ceftriaxone was the most commonly prescribed antibiotic across Internal Medicine, surgical, and Obgyn cases. Based on the Gyssens analysis, antibiotic use was classified into categories 0, I, IIB, IIIA, IIIB, and V, with the highest proportion observed in category IIIB. Overall, the findings indicate that antibiotic use at Hospital X, Malang Regency predominantly falls into category IIIA, suggesting issues related to the duration of therapy.